DA'WAH DEVELOPMENT: PARTICIPATION OF MOSQUE YOUTH IN THE VILLAGE (Study in Paya Bengkuang Village, Gebang District, Langkat, North Sumatra, Indonesia) - Andini, Yulia; Putra, Ilham Mirzaya; Arifin, Zainal (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2023)
The study aims to describe: (1) Youth Participation of the Sri AlHidayah Mosque in the development of da'wah; (2) Factors that support and hinder the development of da'wah in the village of Paya Bengkuang, Gebang District. This research uses a descriptive research type, through a qualitative approach. Sources of data obtained from primary and secondary data sources. The information needed can be obtained from interviews, observation, and documentation. It was conducted at the Sri Al-Hidayah Mosque, Gebang sub-district. In data analysis techniques using data reduction, data presentation, and drawing conclusions and verification. The conclusions of the study are: (1) The most dominant participation of young mosque members is mobilizing resources from the community because people care about assistance for mosque youth either in the form of funds, energy, or thoughts. This can also be influenced by the young members of the mosque who have good behavior and are polite and warm-hearted. Meanwhile, a weak indicator of mosque youth participation is the part involving individuals in organizational activities to mobilize community participation. It is because some youth members of the mosque are busy with their respective duties. (2) The supporting factor of this research is the existence of assistance in the form of donors, and staff from the local community, while the inhibiting factor is the lack of self-awareness from youth, and the community to play an active role in the development of da'wah in Paya Bengkuang village.